Physical and energy requirements of competitive swimming events - Pyne, D. B.; Sharp, R. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
The aquatic sports competitions held during the summer Olympic Games include diving, open-water swim- ming, pool swimming, synchronized swimming, and water polo. Elite-level performance in each of these sports requires rigorous training and practice to develop the appropriate physiological, biomechanical, artistic, and strategic capabilities specific to each sport. Consequently, the daily training plans of these athletes are quite varied both between and within the sports. Common to all aquatic athletes, however, is that daily training and preparation consumes several hours and involves frequent periods of high-intensity exertion. Nutritional support for this high-level training is a critical element of the preparation of these athletes to ensure the energy and nutrient demands of the training and competition are met. In this article, we introduce the fundamental physical requirements of these sports and specifically explore the energetics of human locomotion in water. Subsequent articles in this issue explore the specific nutritional requirements of each aquatic sport. We hope that such exploration will provide a foundation for future investigation of the roles of optimal nutrition in optimizing performance in the aquatic sports.